DISTORSI UMAT ISLAM ANDALUSIA: PERSPEKTIF PENDIDIKAN POLITIK - Fatikhah Fatikhah (UIN K.H. Abdurrahman Wahid Pekalongan, 2009)
In Islamic civilization history, Andalusia is an area located in Spain—the populous and the second largest island of seventeen areas forming Spain—whose capital city is Seville. Islam, historically, arrived at Andalusia during 711 under the commander Walid bin Abdul Malik from Umayyad dynasty in Damaskus. All of these because of the merit of Tarif bin Malik, Thariq bin Ziyad, Musa bin Nusair. After the conquest of Andalusia in Spain, Islamic administration was formed soon with various types of administrative formation. Ironically, however, Muslim community that had developed rapidly could be shoved aside by Christian empire so that the only thing left is historical ruins. From this historical phenomenon, political education that can be taken is that Muslim community should be united in a nation, brotherhood, and not be bewitched by profanity and power, which finally will cause disunity and destruction of religion and state.